Optimal conditions for opening of membrane pore by amphiphilic peptides - Kabelka, Ivo; Vácha, Robert (The Journal of chemical physics, 2015)
Amphiphilic peptides can interact with biological membranes and severely affect their barrier and signaling functions. These peptides, including antimicrobial peptides, can self-assemble into transmembrane pores that cause cell death. Despite their medical importance, the conditions required for pore formation remain elusive. Monte Carlo simulations with coarse-grained models enabled us to calculate the free energies of pore opening under various conditions. In agreement with oriented circular dichroism experiments, a high peptide-to-lipid ratio was found to be necessary for spontaneous pore assembly. The peptide length has a non-monotonic impact on pore formation, and the optimal length matches with the membrane thickness. Furthermore, the hydrophobicity of the peptide ends and the mutual positions of peptides on the membrane play a role.
Keywords: lipidy; povrchově aktivní látky; peptidy; Monte Carlo Method; metoda Monte Carlo; Peptides; Lipids; hydrofobní a hydrofilní interakce; Surface-Active Agents; Hydrophobic and Hydrophilic Interactions